When fiscal recentralisation meets urban reforms: Prefectural land finance and its association with access to housing in urban China. (August 2015) - Fu, Qiang
By retrieving household-level information from 127, 938 household heads and fiscal data from 177 prefectures located in eastern and central China, this research quantifies the net association between land finance and urban housing tenure. While the results demonstrate that in 2005 China's urban housing market remained stratified and simultaneously favoured individuals possessing economic, political and human capital, the key finding is that, net of other household- and prefecture-level effects, land finance is significantly and negatively associated with local homeownership. Moreover, both the demand and supply sides of the urban housing market contribute to such net association. By demonstrating the internal links between urban housing and local finance, this research not only provides a more holistic view of housing stratification during institutional changes but also lends empirical support to conceptual frameworks that explain a territory-based coalition between local governments and selective enterprises.